Simultaneous quantification of two steroidal glycosides after oral gavage of Marsdenia tenacissima extract in rats using a LC‐MS/MS method. (16th September 2014) - Wang, Wei; Sun, Wei; Dong, Lei; Qu, Xiaotong; Shi, Jin; Li, Ke‐Jun; Li, Bing; Ma, Da‐Peng
Abstract: A specific, sensitive and accurate analytical LC‐MS/MS assay was developed for the simultaneous determination of two steroidal glycosides, tenacissoside H and tenacissoside I, in rat plasma. An Agilent ZORBAX SB‐C18 column was used with an isocratic mobile phase system composed of methanol–water–formic acid (70:30:0.1, v/v/v) at a flow rate of 0.3 mL/min. The analysis was performed on a positive ionization electrospray mass spectrometer via selected reaction monitoring mode scan. One‐step protein precipitation with acetonitrile was chosen to extract the analytes from plasma. The lower limits of quantification were 0.9 ng/mL for tenacissoside H and tenacissoside I. The intra‐ and inter‐day precisions were 2.03–11.56 and 3.76–11.62%, respectively, and the accuracies were <110.28% at all quality control levels. The validated method was applied to a pharmacokinetic study in rats after oral gavage of Marsdenia tenacissima extract. Copyright © 2014 John Wiley & Sons, Ltd.